Penguatan Wilayah Perbatasan: Studi Kasus Pulau Sebatik Kabupaten Nunukan Provinsi Kalimantan Timur - Baskoro Wicaksono (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2013)
This study describes the border management policy conducted by the central government, province of East Kalimantan and Nunukan. Policies such as the establishment of regulatory, institutional strengthening, programs and infrastructure development. The policy is getting good response from the elite and the masses. On the other hand policy makers have expectations of local communities border synergism Sebatik Island in order to build and develop the border areas so as to break the chain of dependence on Malaysia. The research was conducted in Sebatik Island, East Kalimantan province Nunukan with the formulation of the problem (a) what policies are oriented to maintain borders, (b) How is the public response to government policy, (c) What are your expectations of policy makers in local communities to regional border. This study used qualitative methods to phenomenological research strategy. Techniques of data collection in this study using two ways, namely in-depth interviews and secondary data view Results indicate that the existing policy of both the central and provincial to district borders do not solve the problem because it is made on the island of Sebatik with other border regions. The policy does not include local knowledge, where it is desperately needed by the people Sebatik. In addition to policies on programs and infrastructure development of the center, the district adopted a policy of inaction against the illegal cross-border trade, which on the one hand against the rules but if enforced then people can not perform economic activities that impact well-being. Policies like this gets a positive response from the public. Expectations for the future border policy is to load local content or local knowledge.